2023
DOI: 10.3390/coatings13101727
|View full text |Cite
|
Sign up to set email alerts
|

Strong Interface Interaction of ZnO Nanosheets and MnSx Nanoparticles Triggered by Light over Wide Ranges of Wavelength to Enhance Their Removal of VOCs

Xingfa Ma,
Xintao Zhang,
Mingjun Gao
et al.

Abstract: The characteristics of the surface and interface of nanocomposites are important for exerting multi-functional properties and widening interdisciplinary applications. These properties are mainly depending on the electronic structures of materials. Some key factors, such as the surface, interface, grain boundaries, and defects take vital roles in the contribution of desired properties. Due to the excellent sensitivity of the QCM (quartz crystal microbalance) device, the surface and interface features of the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 98 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…Further, since there are many ways to passivate the defects of nanocomposites based on their interfacial electronic interactions, carbon nanofibre was derived using carboxymethyl cellulose under a similar reaction condition, and the interaction between carbon nanofibre and Cu nanoparticles was studied for defect passivation, because Cu nanoparticles are electron-rich materials [77]. In another previous report [78], a ZnO/MnS x nanojunction was constructed to narrow the bandgap of wide-bandgap materials, which showed that the absorption of the resulting nanocomposite was extended to part of the NIR region due to the introduction of an impurity level or defect level. Photocurrent signals were obtained from the visible light region to part of the NIR.…”
Section: Introductionmentioning
confidence: 99%
“…Further, since there are many ways to passivate the defects of nanocomposites based on their interfacial electronic interactions, carbon nanofibre was derived using carboxymethyl cellulose under a similar reaction condition, and the interaction between carbon nanofibre and Cu nanoparticles was studied for defect passivation, because Cu nanoparticles are electron-rich materials [77]. In another previous report [78], a ZnO/MnS x nanojunction was constructed to narrow the bandgap of wide-bandgap materials, which showed that the absorption of the resulting nanocomposite was extended to part of the NIR region due to the introduction of an impurity level or defect level. Photocurrent signals were obtained from the visible light region to part of the NIR.…”
Section: Introductionmentioning
confidence: 99%